Zone-based congestion detection and control using routing method on the internet. (15th November 2007) - Ahmed, Ashraf Uddin; Saito, Senro; Cheng, Zixue; Takizawa, Makoto
The rapid growth of information technology has resulted in severe congestion problems in the internet. Due to micro-level congestion (such as link and router), it is hard to detect and control the congestion from the internet. To reduce and/or overcome this problem, we introduce, a macro-level congestion detection mechanism and congestion control method across the internet. Here, a zone is a collection of hundreds or thousands of networks situated in a geographical region. A zone has a zone-manager and border routers; they can cooperate with each other by controlling information. Using our method, zones can prevent congestion and produce better zone performance.